Solutions manual principles of information systems for management - Niv Ahituv (BETech, 1994)
This book is divided into five major parts. Part A includes answers to the review questions and problems at the end of text chapters. Part B presents proposed solutions for the case assignments. Part C includes an outline for an assigned preliminary system study study report and an example of such a report. Part D includes answers to the questions in the minicases provided at the ends of chapters. Part E contains transparency masters of the figures and tables in the text